ANALISIS KESULITAN SISWA SMP DALAM MENYELESAIKAN SOAL MATEMATIKA MATERI BANGUN RUANG SISI DATAR PADA PANDEMI COVID - 19 - utami, yunisa rizki (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study intends to find the difficulties faced by students when solving problems in the form of descriptions based on the indicator questions as follows: mentioning the elements of flat-sided shapes, identifying flat-sided geometrical nets, calculating the surface area of prisms, solving problems related to prism volume. , solve problems related to the surface area of the beam. The difficulties often faced by students include applying formulas, understanding concepts and difficulties when doing calculations. The method used in this research is descriptive qualitative. The data was collected based on the description of the questions given to the students and then the students' answers were checked and analyzed. The place where this research was carried out was SMP Negeri 10 Cimahi in class IX even semester of the 2020-2021 academic year. The population of this research is all students of SMP class IX in Cimahi. 32 students in grades IX – F became the research subjects. The data was obtained from the instrument in the form of a description test given to students. The research data shows that most students have difficulty in working on problems related to the surface area of prisms and beams, the percentage of errors is above 50%, other factors that influence student errors include the lack of understanding and students' definitions of surface area and volume of flat-sided shapes, students find it difficult to apply formulas and are often confused in solving problems using the formula for the surface area of the flat side and the volume of the flat side